Comparison of Safety and Efficacy of Different Class of Anti-hypertensive Drugs Prescribed in Patients with Hypertension - Suthar, Jalpa; Patel, Amishi; Shelat, Bhavik (Indian Journal of Pharmacy Practice)
Background: Hypertension is considered as key indicator for various cardiovascular diseases. Blood pressure is the pressure of blood on arterial walls. The use of antihypertensive drugs is increased worldwide. Hypertension treatment strategy varies widely in terms of initial drug of choice from diuretic to ACEIs/ ARBs/ CCBs and from monotherapy to combination therapy. Objectives: To compare the safety and efficacy of different class of Antihypertensive drugs prescribed in patients with hypertension. Methods: A Prospective observational and longitudinal study which included 150 newly diagnosed hypertensive patients attending medical outpatient department of Sheth HJ Mahagujarat Hospital, Nadiad. Demographic details and baseline blood pressure of the patients were recorded. Patients were followed up after 15 days and one-month period of treatment. Adverse effects were noted at the time of treatment. Results: The mean age of patients 55 years in which both genders were equally exposed. Diabetes Mellitus was major associated condition and patients above 50 years were at high risk for hypertension. Patients receiving ARBs showed significant control in blood pressure (p=0.03) as monotherapy when compared with other Anti-hypertensive drugs. In FDCs, Losartan + Hydrochlorothiazide (p=0.03, 0.005), Telmisartan + Metoprolol Succinate (p=0.00002, 0.005) and Losartan + Amlodipine (p=0.03, 0.0003) proved significance. Reported adverse effects were recorded at the time of treatment as safety parameter. Conclusion: Hypertension was most common in patients above 50 years. ARBs were most prescribed as monotherapy. In FDCs most suitable combinations were with ARBs with few adverse effects.
Keywords: Hypertension; Safety; Efficacy; ARBs; FDCs.